2006
DOI: 10.1038/modpathol.3800563
|View full text |Cite
|
Sign up to set email alerts
|

Early-onset gastric cancers have a different molecular expression profile than conventional gastric cancers

Abstract: Many studies examine the molecular genetics of gastric cancer, but few look at young patients in particular and there is no comparison of molecular expression between early-onset gastric cancer (< or = 45 years old) and conventional gastric cancers. Expression of cycloxygenase-2 (COX-2) is elevated in gastric adenocarcinomas compared to non-neoplastic mucosa, and in light of studies showing reduced risk of gastric cancer in nonsteroidal anti-inflammatory drug users, we have chosen to investigate the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 45 publications
6
82
1
1
Order By: Relevance
“…Of note, 94 of the early-onset gastric cancers and 90 cases of conventional gastric cancers described in Table 3 have been published previously, 9 where a statistically significant difference (Po0.001) was seen between early-onset gastric cancer and conventional gastric cancer, with early-onset gastric cancer having a COX-2 lowexpressing phenotype as well as a statistically significant association with the intestinal phenotype (Po0.001). This statistical difference remained COX-2 promoter polymorphism -765 G4C and gastric cancers R Sitarz et al when adjusted for histology and location using a binary logistic regression model (Po0.001).…”
Section: Cox-2 Expression In Gastric Cancermentioning
confidence: 91%
See 2 more Smart Citations
“…Of note, 94 of the early-onset gastric cancers and 90 cases of conventional gastric cancers described in Table 3 have been published previously, 9 where a statistically significant difference (Po0.001) was seen between early-onset gastric cancer and conventional gastric cancer, with early-onset gastric cancer having a COX-2 lowexpressing phenotype as well as a statistically significant association with the intestinal phenotype (Po0.001). This statistical difference remained COX-2 promoter polymorphism -765 G4C and gastric cancers R Sitarz et al when adjusted for histology and location using a binary logistic regression model (Po0.001).…”
Section: Cox-2 Expression In Gastric Cancermentioning
confidence: 91%
“…9 In 51 cases, it was performed on whole-tissue sections and in six cases tumor tissue was no longer available or unassessable on the TMA. Sections (4 mm) were deparaffinized and antigen was retrieved by 10 min of boiling in 0.01 M Na-citrate buffer (pH 6), followed by immersion in 0.03% hydrogen peroxide in methanol for 20 min.…”
Section: Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…Carcinogenesis is an accumulation of genetic events during aging, and the age-dependent increase in the incidence of GC demonstrates a steep slope (28). The increased risk of GC in the elderly indicates that gene-environment interactions may be involved in carcinogenesis, and the LMP7-145 genotype effects tended to be age-specific.…”
Section: Discussionmentioning
confidence: 99%
“…In conventional gastric cancer (presenting >45 years old), environmental factors play a more important role, compared to early onset gastric cancer (EOGC, presenting at ≤45 years old) where it is postulated that genetic factors may be more important [20]. We have previously shown that molecular differences exist between conventional gastric cancer and EOGC [4][5][6][29][30][31][32]. Apart from cases of hereditary gastric cancer, it remains unclear what predisposes the young patients to gastric cancer at such an early age.…”
Section: Introductionmentioning
confidence: 99%